Trends and evolution of agile branding: a bibliometric analysis. - Pöhlmann, Michaela; Jambrino-Maldonado, Carmen; De-las-Heras-Pedrosa, Carlos; Seitz, Jürgen (My University, 2024)
As today’s environment constantly changes, scientific and practical literature suggests that brands must be managed more agilely. Agile branding, characterized by stakeholder involvement, adaptability, and flexibility, emerges as an innovative approach for companies to navigate dynamic markets to ensure that they remain sustainably relevant and competitive. Yet, no bibliometric analysis has been conducted on agility related to branding to date. This paper aims to illustrate and analyze the trends and evolution of agile branding by applying bibliometric methods to the scientific article literature produced between 1996 and 2023. The results of a systematic literature review are presented, and the findings of the bibliometric analysis of 70 publications listed in the Web of Science Core Collection database are evaluated. Furthermore, visualization and interpretation of bibliometric networks related to citations and publications, publication titles, keywords, authorship, and affiliations with the software VOSviewer is included. This bibliometric analysis shows that the number of scientific studies on agility related to branding has increased mainly since 2008, reaching its peak in 2022, indicating a growing research interest. The study reveals that much more research needs to be conducted on how brands can be managed more agilely and dynamically to compete in a fast-moving world.
Keywords: Marcas (Marketing); Agility; Agile branding; Brand agility; Branding process; Strategic brand management; Agile marketing; Bibliometric analysis